Changing relationships between authors and publishers: Lithuania Major in the first half of the 19th century (Libellarium: journal for research in the field of information and related sciences, 2014)
The changing relationship between authors and publishers was a phenomenon related to the model of modern book publishing business which began to emerge in Lithuania Major, as well as throughout much of Central and Eastern Europe in the early 19th century. The topic of this research is the legal framework established in 1830 as part of Russian censorship laws intended to regulate property rights of authors and publishers, which was also applied in the occupied territory of Lithuania. Different sources and methods were used in this article to answer to the following questions: “How were the rights and obligations of authors and publishers understood in documents regulating publishing activities in Lithuania Major in the first decades of the 19th century (i.e. before 1830)?”; “How was this concept legitimized in the first legal enactments regulating copyrights (i.e. after the introduction of regulations)?”; “How were these mutually useful relationships reflected in Lithuanian book publishing before the Russian occupational government imposed radical measures to restrict Lithuanian national culture and publishing in 1864?” The main sources of data were the 19th century official and unofficial documents regulating publishing activities (including, most importantly, the censorship laws of the time) and archival materials documenting the activities of Lithuanian private publishers and book authors of the time, such as correspondence and documentation on the activities of publishing institutions.
Keywords: private publishing business; copyrights; authorship payments; Lithuania Major